2003
DOI: 10.1074/jbc.m302536200
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the G Protein-coupled Receptors Rhodopsin and Opsin in Native Membranes

Abstract: Here, we have determined by atomic force microscopy the organization of rhodopsin in native membranes obtained from wild-type mouse photoreceptors and opsin isolated from photoreceptors of Rpe65؊/؊ mutant mice, which do not produce the chromophore 11-cisretinal. The higher order organization of rhodopsin was present irrespective of the support on which the membranes were adsorbed for imaging. Rhodopsin and opsin form structural dimers that are organized in paracrystalline arrays. The intradimeric contact is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

65
646
2
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(716 citation statements)
references
References 56 publications
(74 reference statements)
65
646
2
3
Order By: Relevance
“…Specifically, agonists accelerated crosslinking of a set of residues on a different TM4 face than the one preferred by the inverse agonist, while diminished crosslinking was recorded for residues on the interface preferred by the inverse agonist. Thus, the TM4 dimer interface of the inverse agonist-bound D2DR homo-dimer, which is consistent with the 1N3M intradimeric interface of rhodopsin 5 [ Fig. 1(A)], rearranges into an alternative TM4 interface corresponding to the agonist-bound conformation of the D2DR dimer.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Specifically, agonists accelerated crosslinking of a set of residues on a different TM4 face than the one preferred by the inverse agonist, while diminished crosslinking was recorded for residues on the interface preferred by the inverse agonist. Thus, the TM4 dimer interface of the inverse agonist-bound D2DR homo-dimer, which is consistent with the 1N3M intradimeric interface of rhodopsin 5 [ Fig. 1(A)], rearranges into an alternative TM4 interface corresponding to the agonist-bound conformation of the D2DR dimer.…”
Section: Introductionsupporting
confidence: 72%
“…This new perspective has focused attention on the need to study dynamic three-dimensional (3D) models of oligomeric GPCRs to understand the structural details of the molecular mechanisms associated with ligand-induced activation of GPCR oligomers, and concurrently develop new drugs. [2][3][4] The first 3D molecular model of a GPCR oligomer was proposed by Liang et al 5 (PDB: 1N3M) using data from atomic force microscopy maps of rhodopsin in its native disk membrane. 6 This model showed an arrangement of rhodopsin molecules in two dimensional arrays of dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, proteins that form oligomeric assemblies are highly susceptible to functional changes at even modest pressures (Hazel and Williams, 1990;Morita, 2010). The dimer interface for most GPCRs, including cephalopod and bovine rhodopsins, has been reported to lie on the outer face of helices IV and V (Bockaert and Pin, 1999;Bulenger et al, 2005;Fotiadis et al, 2003;Liang et al, 2003) where the residues that we have identified as being under selection in both fish and cephalopod opsins are located.…”
Section: Evolution Of Protein Compressibilitymentioning
confidence: 76%
“…In this respect, the highest resolution information available thus far comes from X-ray crystallography and atomic force microscopy (AFM) measurements on rhodopsin, opsin, b 2 -AR and CXCR4 chemokine receptor, as well as from cysteine crosslinking experiments on D 2 receptor (D 2 R), and disulphide trapping experiments on 5HT 1c receptor [22][23][24][25][26][27][28][29]. With regard to rhodopsin, the geometrical constraints from AFM measurements led to the proposal of a semi-empirical model of a higher order rhodopsin structure [22]. According to this model, two monomers of rhodopsin interact with each other through the second extracellular loops (EL2), the second cytoplasmic loops (IL2), and H4 and H5 of both monomers.…”
Section: Introductionmentioning
confidence: 99%